2013
DOI: 10.1590/s0100-736x2013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho ponderal de bovinos Nelore suplementados com fontes alternativas de fósforo

Abstract: ABSTRACT.-Lemos G.C., Costa R.M., Neto M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There is a search to optimize phosphate rock from Cajati as an alternative source of phosphorus. Lemos et al (2013) sought to use the rock in the diet of Nellore cattle, as Bernardi and Oliveira (2021) sought to associate the phosphate rock of Cajati with zeolite minerals to nourish the alfalfa crop.…”
Section: Discussionmentioning
confidence: 99%
“…There is a search to optimize phosphate rock from Cajati as an alternative source of phosphorus. Lemos et al (2013) sought to use the rock in the diet of Nellore cattle, as Bernardi and Oliveira (2021) sought to associate the phosphate rock of Cajati with zeolite minerals to nourish the alfalfa crop.…”
Section: Discussionmentioning
confidence: 99%
“…Although phosphorus metabolism can be dependent on Ca, Prados et al (2015) obtained results similar to that of this study, when evaluating the effects of diets containing three different concentrations of Ca (0.18, 0.30, and 0.48% in DM) and three levels of P (0.22%, 0.24 and 0, and 26% in DM) on the intake, nutrient digestibility, and performance of crossbred cattle during the finishing period in feedlot. Lemos, Costa, Neto, and Malafaia (2013) and NRC (2000) have shown that the recommended P requirements may overestimate the dietary requirements of beef. A study conducted by Lemos et al (2013) did not show differences in the performance of Nellore cattle confined and supplemented or not with P for 134 days.…”
Section: Discussionmentioning
confidence: 99%
“…Lemos, Costa, Neto, and Malafaia (2013) and NRC (2000) have shown that the recommended P requirements may overestimate the dietary requirements of beef. A study conducted by Lemos et al (2013) did not show differences in the performance of Nellore cattle confined and supplemented or not with P for 134 days. Costa et al (2016), using different levels of P supplementation, also did not find an apparent relationship between the levels of P supplement and fertility rate of cows.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, a supplementation with high concentrations of P, is a waste if in excess of requirement and if made without the knowledge of nutritional and clinical examination of herds and a constant technical assistance, can represent an unnecessary cost for livestock production. Additionally, according to several estimates, mineral supplementation may constitute 10-20 % of the operational cost of beef cattle raised in grasslands, which justifies the research studies on the subject in Brazil (Peixoto et al 2003;Lemos et al 2013;Malafaia et al 2004Malafaia et al , 2014). This experiment did not test if there would be a response to a zero P supplementation, but rather tested a reduction in P concentration, because it was carried out in a private farm which the main objective is to achieve profit.…”
Section: Discussionmentioning
confidence: 99%